Environmental impact of intensive horticulture practices on groundwater content of nitrates, sodium, potassium and pesticides - Pinto, Edgar (2021)
Recent changes in agricultural practices during the last 20th century have significantly contributed to increase the concentrations of pollutant substances is water, soil and air. Groundwater is a valuable natural resource and as such should be protected from deterioration and chemical pollution. A monitoring program of nitrate, nitrite, potassium, sodium and 28 pesticides was carried out in water samples from an intensive horticulture area in a vulnerable zone from North of Portugal. Eight collecting points were selected and water analyzed in five sampling campaigns, during one year.